2010
DOI: 10.3109/03008200903318261
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2, collagenase, and cell death responses depend on cyclical load magnitude in an explant model of tendinopathy

Abstract: Tendinopathy is a significant clinical problem that can result from repetitive activity. While the precise etiology of this condition remains unclear, the cellular response to cyclical loading is believed to have a contributory role to the pathology of tendinopathy. This study examined the short-term biochemical response of avian flexor digitorum profundus tendon to repetitive cyclic loadings of varying magnitude. An in vitro tendon explant model was utilized to apply four levels of haversine tensile stress (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Consistent with the present findings, Riley (3) suggested that tendon matrix damage is the primary event, overwhelming the ability of the resident cell population to repair structural defects and degradation of the extracellular matrix may affect the structural properties of the tendon. Previous studies (27,28) have also reported that fibronectin is markedly increased following tendon injury when compared with the levels in the normal tendon and consequently has been implicated in cell adhesion, migration and differentiation at the site of injury. Therefore, the present study indicates that these integrin genes associated with focal adhesion have crucial roles in tendinopathy development.…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with the present findings, Riley (3) suggested that tendon matrix damage is the primary event, overwhelming the ability of the resident cell population to repair structural defects and degradation of the extracellular matrix may affect the structural properties of the tendon. Previous studies (27,28) have also reported that fibronectin is markedly increased following tendon injury when compared with the levels in the normal tendon and consequently has been implicated in cell adhesion, migration and differentiation at the site of injury. Therefore, the present study indicates that these integrin genes associated with focal adhesion have crucial roles in tendinopathy development.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, experiments were performed on tissues that had previously been frozen, and as such cell response could not be studied. However, it has previously been reported that cyclic loading of viable tendon explants in vitro results in increased cell death and production of prostaglandin-E2 and collagenases at high magnitudes of applied load [55]. rsif.royalsocietypublishing.org J. R. Soc.…”
Section: Discussionmentioning
confidence: 99%
“…When the rotator cuff is torn, interleukin-1β (IL-1β) is produced in the torn tendon, stimulating cyclooxygenase 2 (COX-2) expression and subsequent prostaglandin E2 (PGE2) production [2]. In in vitro model systems, mechanical loading often don fibroblasts or isolated tendon increases PGE2 production and release [3,4,5]. Exogenous PGE2 treatment inhibits tendon fibroblast proliferation and collagen synthesis in vitro [6] and causes localized tendon disorganization and degeneration in vivo [7,8].…”
Section: Introductionmentioning
confidence: 99%